Bioekologi Bunga Bangkai (Amorphophallus titanum (Becc.) Becc.) Di Desa Muara Hemat Resort Kerinci Selatan Taman Nasional Kerinci Seblat - Nursanti Nursanti; Cory Wulan; Monica Ria Felicia (Jurnal Silva Tropika, 2019)
Amorphophallus titanum is native to Sumatra's rainforest that was first recognized in the world of science after it was discovered by Dr. Odoardo Beccari in 1878 in the Lembah Anai, West Sumatra. Amorphophallus titanum is protected by the Government Regulation Number 7 in 1999 and being categorized as Vulnerable to Red List Data Book issued by IUCN (International Union for Conservation of Nature and Natural Resources) in 1997. This study aims to examine the natural population of Amorphophallus titanum and analyze the pattern of its distribution in Muara Hemat Village, Kerinci Seblat National Park. The data were collected with 3 hectars of sampling area divided into 3 lines (transect) measuring 10 m x 1000 m. The distance between each transect is 1000 m. Each transect is divided into plots measuring 10 m x 10 m, resulting in a total of 300 plots. The dispersal pattern of A. titanum was analyzed by Morisita Index formula. Based on research that has been done, the population of A. titanum were 83 individuals which were located in 51 of 300 research plots. The density of A. titanum was 27.67 individuals/hectar. Through the Morisita index calculation, it is known that the distribution pattern of A. titanum in Muara Hemat Village is clumped (Ip = 0.50).